O exercício da tutela arbitral pela Câmara Nacional de Resolução de Disputas no futebol associado - Fachada, Rafael Terreiro (2023)
This thesis analyses and ponders on how the National Dispute Resolution Chamber (CNRD), a judicial/adjudicating body provided by the Brazilian Football Confederation’s Statutes, structures its adjudication procedures for serving the brazilian football associated system stakeholders. To do so, it introduces FIFA’s football associated system, that is, its bases, its development and its network. Then, it explores the jurisdiction and it’s civil law companion (competence) concepts, including regarding the role of government-level decisions as well as dispute resolution through arbitration. Furthermore, having a systemic setting and legal conceptualization as basis, the analysis discusses possible ways to solve disputes in the football market: i.e., via FIFA judicial/adjudicating bodies when present a prima facie international dimension to the dispute, and/or via each national association’s national dispute resolution chamber when it has undisputed jurisdiction. Given practical conflict of law issues, this paper narrows down on the way in which the NDRC integrates this football dispute resolution global network. As such, it addresses the CNRD jurisdiction pertaining to the CBF statutes and regulations, especially when there is a forum-shopping clause or an arbitration agreement. Finally, it addresses the CNRD stakeholders’ decision compliance